A biologically inspired approach to feasible gait learning for a hexapod robot - Belter, Dominik; Skrzypczyński, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
The objective of this paper is to develop feasible gait patterns that could be used to control a real hexapod walking robot.These gaits should enable the fastest movement that is possible with the given robot?s mechanics and drives on a flatterrain. Biological inspirations are commonly used in the design of walking robots and their control algorithms. However,legged robots differ significantly from their biological counterparts. Hence we believe that gait patterns should be learnedusing the robot or its simulation model rather than copied from insect behaviour.
Keywords: evolutionary learning; legged robots; gait generation; model identification; reality gap